Thermal-hydraulic tests of finned recirculating cooling equipment. (November 2019) - Lychakov, V D; Egorov, M Yu; Matyash, A S; Shcheglov, A A
Abstract: The article analyzes the experience of thermal-hydraulic experimental studies of various types of finned tube heat exchangers by the Power Equipment Test Facility of JSC "NPO CKTI". The method of testing the air-cooled heat exchanger with finned heat exchange surface for recirculation cooling units ROPE(A)-2400/253-1 of the Belarusian NPP was developed. The results of the tests according to the developed method are necessary to confirm the thermal characteristics of the heat exchange equipment of the NPP before the start of industrial operation.